(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Objective: This prospective observational study aimed to analyze the prescribing patterns and medication adherence of antimicrobials in diabetic foot patients in the department of general surgery at a tertiary care hospital. A total of 120 diabetic foot patients were assessed in this study for the period of 6 months. This study mainly describes about the antimicrobial usage and current prescription patterns of antimicrobials in patients of diabetic foot ulcer (DFU). By empowering patients to understand the rationale behind their treatment regimens and the consequences of non-adherence, healthcare providers can enhance patient engagement and promote self-management. Medication adherence is effectively measured by Morisky Medication Adherence Scale 8-item (MMAS-8). Purpose of the Study: The purpose of this study is to analyse the prescribing patterns and medication adherence of antimicrobials in diabetic foot patients in the department of general surgery. Evaluating the antimicrobial usage by MMAS-8. Methods: This study was carried out in a tertiary care teaching hospital located in South India, over 6 months from October 2023 to March 2024. The study assessed the antimicrobial usage in the management of DFU, current prescription patterns of antimicrobials, and Medication adherence. Conclusion: In conclusion, this study provided insights into prescribing patterns and medication adherence in diabetic foot patients receiving antimicrobial therapy, aiding the understanding of DFU management. Variations in prescription patterns highlight the need for standardized guidelines to optimize treatment and minimize antimicrobial resistance risks. Improving medication adherence and patient education is crucial for better clinical outcomes and reduced healthcare burden associated with diabetic foot complications.